Assessing Jamaica's Logistics Hub Initiative and Its Implications for Sustainable Development - Reid, Shemar; Johnson, Corey (International Journal of Scientific Research and Management (IJSRM), 2024)
This study looks at the Jamaica Logistics Hub Initiative (JLHI), a deliberate initiative to convert Jamaica into a major participant in global commerce and logistics. Using a mixed-methods approach, the study examines economic indicators, environmental consequences, and alignment with sustainable development objectives from 2010 to 2022, including time periods prior to and following the initiative's 2013 first appearance. The findings show considerable economic benefits, such as faster GDP growth, higher foreign direct investment, and job creation in logistics-related industries. However, the report notes several problems, notably in terms of environmental sustainability and the need to improve export competitiveness. The JLHI's connection with the SDGs is reviewed, highlighting positive contributions to economic growth and global alliances, while recognizing opportunities for improvement in the management of the environment. The study concludes that the JLHI's long-term performance is dependent on combining economic goals with environmental sustainability and social equality. Recommendations include improving logistical performance, creating value-added services, introducing green technology, and prioritizing workforce development. This thorough research provides useful insights for policymakers and stakeholders, adding to the current discussion on sustainable logistics hub development in small island developing states.